Compelling the Muslim Subject: Memory as Post-Colonial Violence and the Public Performativity of "Secular and Cultural Islam" - Mas, Ruth (The Muslim world (Hartford), 2006)
The intellectuals, members of The Association of the Manifesto of Liberties, self-identified as women and men, carriers of the values of laïcité and connected together by their unique histories and in different ways to Islam, and registered two overriding concerns: a general marginalization of Muslims within European societies, and the divisive splits within the Muslim communities that were being exacerbated by the so-called Cartoon Affair.